Yin-Nourishing and Heat-Clearing Therapy for Radiotherapy-Related Adverse Effects in Nasopharyngeal Carcinoma: A Review - Liu, Lu; Zhao, Yanli; Zhao, Yaxuan (Journal of Contemporary Medical Practice, 2026)
Nasopharyngeal carcinoma is prevalent in southern China, and radiotherapy remains the principal treatment. Despite effective tumor control, radiotherapy often causes oral mucositis, xerostomia, sinusitis, and dermatitis. These adverse effects impair quality of life and may interrupt treatment. This review examines their pathogenesis from biomedical and traditional Chinese medicine perspectives. It then summarizes clinical approaches based on nourishing yin and clearing heat and evaluates pharmacological evidence for representative formulas and medicinal substances. Current findings suggest anti-inflammatory, antioxidant, immunomodulatory, microcirculatory, and tissue-repair effects. However, small samples, heterogeneous interventions, inconsistent outcomes, and indirect mechanistic evidence preclude firm conclusions. Multicenter randomized controlled trials are needed to determine efficacy, safety, optimal timing, and the relationship between pharmacological mechanisms and clinical outcomes.